Civic of Culture: Media, Kaum Muda, dan Mengenali Ke-Istimewaan Yogyakarta - Anissa, Firly (Jurnal Komunikator, 2015)
Ideally local media has special spaces to present special characters of culture in a particular area. The objectives are to improve the pride and sense of belonging as well as cohesive correlation of the society especially the young generation. The study is aimed to investigate an analysis âHow is the role of local media in Yogyakarta, both local TV Jogja TV and mass media Kedaulatan Rakyat in presenting special characters of Yogyakarta culture in shaping Civic culture?â so young generation are able to admit those characters. The object research of local media will be chosen qualitatively during July-August 2014 by looking at the kinds of local culture presented in the medias and analyzing the roles of local media. Choosing both medias was based on the biggest and the most influential local medias in Yogyakarta. The study uses qualitative analysis to investigate local wisdom in the medias, and then the researcher would have focus groups discussion (FGD) to young generations who were born, grown, and living in Yogyakarta at least 20 years. The result of the research is going to give an image of thinking pattern as well as sense of belonging from young generation to see special characters of Yogyakarta..Â Â Â Â Keywords: local media; social culture; young generationÂ Â